A Soft Budget Constraint Explanation for the Venture Capital Cycle - Georg Gebhardt (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2006)
We explore why venture capital funds limit the amount of capital they raise and do not reinvest the proceeds. This structure is puzzling because it leads to a succession of several funds financing each new venture which multiplies the well known agency problems. We argue that an inside investor cannot provide a hard budget constraint while a less well informed outsider can. Therefore, the venture capitalist delegates the continuation decision to the outsider by ex ante restricting the amount of capital he has under management. The soft budget constraint problem becomes the more important the higher the entrepreneur's private benefits are and the higher the probability of failure of a project is.
urn:nbn:de:bvb:19-epub-13378-8
Keywords: G24; G31; D82; 330; Contract Theory; Corporate Finance; Venture Capital